Molecular analysis of the graviperception signal transduction in the flagellate Euglena gracilis: Involvement of a transient receptor potential-like channel and a calmodulin - Häder, Donat-Peter; Richter, Peter; Schuster, Martin; Daiker, Viktor; Lebert, Michael (Advances in Space Research, 2009)
Euglena gracilis, a unicellular, photosynthetic flagellate is a model system for environmentally controlled behavior responses. The organism shows pronounced negative gravitaxis. This movement is based oil physiological mechanisms, which in the past had been only indirectly assessed. It was shown that mechano-sensitive calcium channels are involved in the gravitaxis response. Recent studies have demonstrated that members of the transient receptor potential (TRP) family function as mechano-sensitive channels in several different cell types. We have sequenced part of a TRP gene in Euglena and applied RNA interference (RNAi) to confirm that these channels are involved in graviperception. It was found that RNAi against the putative TRP channel abolished gravitaxis. The genes of three calmodulins were sequences in Euglena, one of which was previously known in its protein structure (cal 1). The other two were unknown (cal 2 and call 3). Cal 2 has been analyzed in detail. The biosynthesis of the corresponding proteins of cal I and cal 2 was inhibited by means of RNA interference to see whether this blockage impairs gravitaxis. RNAi of cal I leads to a long-term loss of free swimming in the cells (while euglenoid movement persists). It induced pronounced cell form aberrations and the division of cells was hampered. After recovery from RNAi the cell showed precise negative gravitaxis again. Thus cal I does not seem to be involved in gravitaxis. In contrast, the blockage of cal 2 has no pronounced influence oil motility and cell form but leads to a complete loss of gravitactic orientation for more than 30 days showing that this calmodulin is an element in the signal transduction chain. The data are discussed in the context of the current model of the gravitaxis signal transduction chain in Euglena gracilis. (C) 2009 COSPAR. Published by Elsevier Ltd. All rights reserved.
Keywords: Euglena gracilis; Gravitaxis; Signal transduction; Mechano-sensitive channel; Calmodulin